The Teaching Skills Accordance to McFarland’s Strategy in Developing Grammatical Concepts Among Middle School Students - Al-Kahtani, Adel Abdullah; Al- Maghribi, Souad Abdullah (Journal of Educational and Psychological Sciences, 2021)
This study aimed to determine the teaching skills accordance to McFarland's strategy in developing grammatical concepts among middle school students, and the study relied on the descriptive (survey) approach, and the study tool was a list that included the necessary teaching skills according to the McFarland strategy- prepared by researchers- judged by (10) Academically from some Saudi universities, The study concluded with identifying the necessary teaching skills according to McFarland's strategy to develop grammatical concepts among middle school students, as it consisted of two axes: the first axis: the strategy of interconnected words and included 10 skills, and the second axis: the strategy for defending views and included 12 skills, where the total percentage of approval Arbitrators on the list of necessary teaching skills according to McFarland's strategy for developing grammatical concepts among intermediate school students, 96.2%, and based on the results, the researchers recommended providing Arabic language teachers with these skills and stating their importance and necessity in teaching the branches of the Arabic language.
Keywords: Teaching skills; McFarland strategy; grammatical concepts; Intermediate stage